Axial stress–strain model developed for rectangular RC columns confined with FRP wraps and anchors. (February 2020) - Isleem, Haytham F.; Tahir, Muhammad; Wang, Zhenyu
Highlights: Axial behavior of concrete columns confined with FRP wraps and anchors. Column parameter effects on compression bevavior of FRP-confined column behavior. Analytical investigation of RC column behavior confined with FRP wraps and anchors. Model development of FRP-confined rectangular RC columns Abstract: It is widely reported that using fiber-reinforced polymer (FRP) as confinement jackets for concrete can significantly enhance its strength and ductility. The confinement effectiveness for rectangular columns has revealed significant enhancements in their strengths, in particular for well-confined columns with a cross-sectional depth of <300 mm. However, for larger-sized columns with a section depth of larger than 300 mm and an aspect ratio of larger than 2.0, the confinement effectiveness is most limited. One of the key solutions to significantly increase the confinement effectiveness is by using a combination of FRP anchors and wraps. For good analysis and design of FRP confinement for rectangular RC columns, a model for the stress–strain behavior of rectangular reinforced concrete (RC) columns confined with FRP wraps and FRP anchors is provided in this paper. The model is mainly based on results from tests reported in recent studies, in which a series of axial compressive tests on a total of 80 FRP-confined rectangular RC columns of large size were conducted. The database included columns with aspect ratios ranging from 1.5 to 4.0. Furthermore, the depth of the section is up to 600 mm. key parameters such as the aspect ratio and size of cross section, number of layers of FRP wraps, volumetric ratio of internal hoop steel reinforcement, and cross-sectional area and configuration of anchors were all considered. All predicting expressions were validated against the test database used in the model calibration. In terms of average absolute error and mean square error, comparisons with other existing expressions were conducted, showing that the expressions of the present model reveal more accuracy. Finally, comparisons revealed the model can estimate the confinement effectiveness and predict the stress–strain relationships of FRP-confined rectangular RC columns with additional FRP anchorage.